Pengaruh Pilates Exercise Terhadap Penurunan Nyeri Haid Pada Remaja - Fitrica, Amelia; Jasmawati, Jasmawati; Hakim, Lukman (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Dysmenorrhea is a menstrual flow disorder/menstrual pain. Dysmenorrhea pain, if not treated immediately, affects a person's mental and physical functions, thus requiring non-medical intervention. A non-drug treatment that can be done is Pilates exercise. Pilates exercise can relax muscle contractions, stimulate the hypothalamus to produce endorphins as a natural sedative, creating a sense of comfort and reducing pain. To investigate the effect of pilates training on reducing menstrual pain in young SMP 14 Palaran. The methodological study is a quasi-experimental study with no equivalent control group design. The research sample consisted of 15 young women using a simple random sampling technique. The Wilcoxon test was used as a statistical test. The results of the Wilcoxon test obtained a significance value (p) of 0.001 andlt; 0.05 (p and lt; a). Pilates training reduces menstrual pain in youth at Junior High School 14 Palaran. Therefore, it is recommended for young people to use Pilates training to reduce the pain of dysmenorrhea, which does not cause side effects by reducing the incidence of dysmenorrhea pain